Manual de los Regalmentos del Agua de Florida: Poderes Reguladores del Estado - Michael T. Olexa; Laura Minton; Dulcy Miller; Sarah Corbett (EDIS)
Este es el documento EDIS FE064, una publicación del Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Publicada Noviembre 2002.